2015
DOI: 10.1002/jbm.b.33332
|View full text |Cite
|
Sign up to set email alerts
|

Designing new biocompatible glass‐forming Ti75‐xZr10NbxSi15 (x = 0, 15) alloys: corrosion, passivity, and apatite formation

Abstract: Glass‐forming Ti‐based alloys are considered as potential new materials for implant applications. Ti75Zr10Si15 and Ti60Zr10Nb15Si15 alloys (free of cytotoxic elements) can be produced as melt‐spun ribbons with glassy matrix and embedded single β‐type nanocrystals. The corrosion and passivation behavior of these alloys in their homogenized melt‐spun states have been investigated in Ringer solution at 37°C in comparison to their cast multiphase crystalline counterparts and to cp‐Ti and β‐type Ti‐40Nb. All tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Various types of metallic glasses (Zr-based [18,19,20], Mg-based, Zn-based, Ca-based, and Ti-based) alloying systems were studied due to their higher strength, lower Young’s modulus, better wear and corrosion resistance, compared to their standardized counterparts [21]. Although regarding the Ti-based metallic glasses reports on systems such as Ti–Zr–Si [15], Ti–Zr–Cu–Pd [20], Ti–Zr–Ni–Be [19] and others can be found in the specific literature, there is a limited number of articles referring to the Ti–Zr–Nb–Si metallic glasses obtained by melt-spinning [15,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of metallic glasses (Zr-based [18,19,20], Mg-based, Zn-based, Ca-based, and Ti-based) alloying systems were studied due to their higher strength, lower Young’s modulus, better wear and corrosion resistance, compared to their standardized counterparts [21]. Although regarding the Ti-based metallic glasses reports on systems such as Ti–Zr–Si [15], Ti–Zr–Cu–Pd [20], Ti–Zr–Ni–Be [19] and others can be found in the specific literature, there is a limited number of articles referring to the Ti–Zr–Nb–Si metallic glasses obtained by melt-spinning [15,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion and passivation behavior of metallic glasses free of toxic elements, namely Ti 75 Zr 10 Si 15 and Ti 60 Zr 10 Nb 15 Si 15 , produced as melt-spun ribbons by Abdi et al for biomedical applications was also studied [21]. Mechanical properties investigations of Ti 75 Zr 10 Si 15 revealed that Nb has the main effect of decreasing the Young’s modulus of the crystalline alloy as well as its hardness, which is due to the stabilization of a significant fraction of a β-type phase [23].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] These BMG corrosion problems hold disadvantages compared to highly resistant alternative implant materials, e.g., Ti, Ti-6Al-4 V, new beta-type Ti-alloys, or simple Ti-based glassformers with only valve-metal-type components. [8,14,33,34] Variations such as partial substitution of critical Cu with more resistant elements, for instance Nb or Ga, can only inhibit but not suppress pitting. Moreover, they deteriorate the GFA.…”
mentioning
confidence: 99%
“…39 MGs possess electrocatalytic behavior and electrochemical hydrogen sorption in alkaline, neutral and acidic media. [40][41][42][43][44][45]47,48 These materials exhibit limited absorption kinetics and hydrogen-tometal (H/M) ratio, and weak electrocatalytic hydrogen activity compared to Pt. However, Pd-metallic glasses (MGs) exhibit a unique collection of properties, i.e., when compared to crystalline Pd, nanostructured Pd-MGs possess lower passivation current density and higher passivation potential, auspicious mechanical strength and hardness along with high wear and fatigue resistance.…”
mentioning
confidence: 99%